2005
DOI: 10.1007/11539902_145
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prediction of Discharges in Manwan Hydropower Using Adaptive-Network-Based Fuzzy Inference Systems Models

Abstract: Forecasting reservoir inflow is important to hydropower reservoir management and scheduling. An Adaptive-Network-based Fuzzy Inference System (ANFIS) is successfully developed to forecast the long-term discharges in Manwan Hydropower. Using the long-term observations of discharges of monthly river flow discharges during 1953-2003, different types of membership functions and antecedent input flows associated with ANFIS model are tested. When compared to the ANN model, the ANFIS model has shown a significant for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Long-term hydrological prediction is of significance for water resource activities, such as reservoir operation [1][2][3][4][5], water resource planning [6][7][8][9], risk management [10][11][12][13], and urbanization [14,15]. Hence, hydrologic time-series forecasting, especially monthly inflow, has triggered great interest in hydrology and water resources fields [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term hydrological prediction is of significance for water resource activities, such as reservoir operation [1][2][3][4][5], water resource planning [6][7][8][9], risk management [10][11][12][13], and urbanization [14,15]. Hence, hydrologic time-series forecasting, especially monthly inflow, has triggered great interest in hydrology and water resources fields [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the research can be promoted rapidly on the basis of our early works on ANN and SVM [8,40,41]. Hence, we choose ANN and SVM for reservoir monthly inflow forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned points, the neuro-fuzzy and neural network approaches can also predict suspended sediment concentration in rivers (Rajaee et al 2009). Other researchers reported good results in applying ANFIS in hydrological prediction (Cheng et al 2005;Firat & Gungor 2008;Zounemat-Kermani & Teshnehlab 2008;Wang et al 2009). Another study developed the ANN model used to forecast groundwater level changes in an aquifer (Tsanis et al 2008) and ANNs have also been shown to give useful results in many fields of hydrology and water resources research (Campolo et al 2003;Alvisi et al 2006;.…”
Section: Introductionmentioning
confidence: 93%
“…The basic rules can be constructed either from a human or automatic generation, where the searching rules using input-output data numerically. There are several types of FIS, namely Takagi-Sugeno, Mamdani, and Tsukamoto (Cheng et al 2005). A FIS of Takagi-Sugeno model was found to be widely used in the application of ANFIS method.…”
Section: Fuzzy Inference Systemmentioning
confidence: 99%